INDONESIA'S TECHNICAL EDUCATION AID TO KENYA: A SOUTH-SOUTH COOPERATION PERSPECTIVE - Dorine Andayi Munyifwa; Yanyan Mochamad Yani; Siti Aliyuna Pratisti (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2026)
South-South Cooperation (SSC) has become a structurally different form of development that is a challenge to the conditionality-based structures of North-South aid. This paper discusses the technical education assistance given by Indonesia to Kenya as a development diplomacy tool in the SSC context, filling a literature gap on how Southern donors use education assistance as a soft power and public diplomacy instrument. Based on qualitative documentary analysis of policy reports, institutional documentation, and peer-reviewed literature, 2009-2025, the study explores three dimensions of analysis: the institutional architecture of SSC in education in Indonesia, how technical education partnerships are aligned with the industrialization agenda of Kenya Vision 2030 and the soft power politics inherent in Indonesian involvement as an emerging Southern donor. The results show that the Indonesian technical education aid, in the form of scholarships, TVET capacity-building, and bilateral memoranda of understanding is a demand responsive, sovereignty-respecting model that fulfills Kenya-reported skills shortage and serves Indonesia development diplomacy goals. This work advances both constructivist explanations of SSC and the literature on public diplomacy by developing technical education as an analytically meaningful yet under-researched tool of Southern Unity.